Financial Policy on Promotion of Supporting Industries for Vietnam: Reality and Recommendation - Minh, Nguyen Ba; Tam, Le Vu Thanh (Archives of Business Research, 2022)
This study aims at analyzing aspects determining supporting industries (SIs) to serve the task of developing such industries. Analyses show that though Vietnamese SIs have obtained considerable improvements related to the scale and effect in recent years, these progresses are still modest and unable to help the manufacturing sector increase its added value and join the global value chain. The results find the following culprits: the financial policies on SI development are not compatible with main trends of market specialization and global value chain; chain of domestic industrial production is till lacking; and inter-industry cooperation is poor. Policy recommendations, therefore, are as follows: establishing the legal infrastructure for SI development, design of a value chain for SIs, building of clusters of SIs, and mechanism for promoting SI development.